Readiness in using online interactive platforms for remote teaching - Siti Fatimah Omar; Haslinda Sutan Ahmad Nawi; Rita Wong Mee Mee; Lim Seong Pek; Tengku Shahrom Tengku Shahdan; Adelaide Woo (Institute of Advanced Engineering and Science, 2021)
Technological advances offer a new shift of change for society. In this era, it is almost impossible to come by without its help. The Malaysian government has invested highly in information and communications technology (ICT) for online teaching and learning at the current time. Digital technologies have been integrated into the teaching and learning process in almost all public or private schools in Malaysia. The use of multimedia tools has enabled learners to understand difficult concepts or ideas and different types of learning preferences. The purpose of the study is to identify pre-service teachers’ perceptions towards using online teaching platforms as a mode of teaching tool in carrying out service-learning in the period of the Covid-19 pandemic. Survey research was carried out on 94 final-year pre-service teachers from diploma in teaching english as a second language. Findings revealed that pre-service teachers had shown positive perceptions of online teaching platforms for remote teaching. Findings had also shown that pre-service teachers preferred blended learning by combining both classroom and online teaching over traditional classrooms per se.